Distaste and nonsense : some critical reflections on the interface between comedy and contemporary art : Master of Fine Arts, Massey University, Wellington - Morrison, Scott (Massey University, 2016)
This thesis investigates, through a largely video and performance based art practice, some of the relationships between Comedy, Contemporary art and psychological defence mechanisms. This body of work aims to challenge some preconceived notions of what comedy in an artistic context can be, including comedy that involves elements of disgust, irony, failure and anti-humour. The research here also attempts to find unique perspectives that have come about through the intersection of specific psychological defence mechanisms, experimental comedy, and contemporary art.
Keywords: Scott Morrison; Criticism and interpretation; Wit and humor in art; Performance art; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Art